Encastrement et nouvelle sociologie économique : de Granovetter à Polanyi et Mauss - Laville, Jean-Louis (Revue Interventions économiques. Papers in Political Economy, 2008)
Le concept d’encastrement s’est imposé dans la nouvelle sociologie économique. Ce texte souligne sa polysémie. Dans une première partie, il rappelle les deux acceptions politique et réticulaire respectivement adoptées par Granovetter et Polanyi. Rapportée à la modernité démocratique, la démarche de Polanyi permet de mettre en évidence un double mouvement caractérisant les rapports entre économie et société, dont les grands traits sont synthétisés dans la deuxième partie. Si l’on adopte une telle lecture, la convergence entre Polanyi et Mauss apparaît alors dans une approche plurielle de l’économie, présentée dans la troisième partie. Selon l’hypothèse esquissée dans la quatrième partie, une telle lecture suggère d’approfondir la teneur des changements institutionnels susceptibles de conforter la pluralité de l’économie, autrement dit de participer à son « ré-encastrement » démocratique. The concept of embeddedness has imposed itself in the New Economic Sociology. This paper highlights the multiple meanings of this term. In a first part, we discuss the political and reticular meanings adopted by Granovetter and Polanyi respectively. In the context of modern democracy, the work of Polanyi shows a double movement characterizing the relations between economy and society, which we develop in the second part. With such a perspective, the convergence between Polanyi and Mauss is highlighted in a plurial approach of the economy, which we discuss in the third part. The hypothesis presented in the fourth part leads us to analyze the content of institutional changes which can confirm the plurality of the economy, and to participate in its democratic « reembeddedness ».
Sociology; Economics
Keywords: GRANOVETTER; Mark; MAUSS; Marcel; 1872-1950; economic sociology; encastrement; niveau d’intégration; sociologie économique

La dépolitisation de la notion de « capital social » : pourquoi pas un retour à Karl Polanyi? - Bibeau, Gilles (Anthropologica, 2008)
Anthropology
Keywords: social capital

Le capital et la question nationale - Maucourant, Jérôme; Tinel, Bruno (Actuel Marx, 2008)
Nations are the forms of political organization which peoples construct for themselves. It is a commonplace to state that globalization tends (for the better) towards the end of nations. However the history of capitalism shows that such a hypothesis is questionable. Globalization is merely a stage in the development of capitalism, which has always leaned on certain nations to secure its deployment: England in the past, the U.S. today. The real question is thus that of the hegemony of one nation over other nations and, ultimately, the question of democracy, the sovereignty of peoples in the face of capital.
Economics
Keywords: democracy; globalization

Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Sociology; Political Science
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER; Max; 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).
History

L'innovation sociale dans les services d'aide a domicile. Les apports d'une lecture polanyienne et feministe. (With English summary.) - Degavre, Florence; Nyssens, Marthe (Revue Francaise de Socio-economie, 2008)
The aim of this contribution is to analyze the dynamic of social innovation of home-care services. Based on the works of Polanyi which analyse socio-economic dynamics and on feminist theories in the field of care, we develop an original grid of analysis developing criteria to grasp the processes of social innovation and to highlight the peculiarities of gender relationships at stake in these services. We also suggest normative criteria to evaluate the quality of social innovation. We apply this conceptual framework to the empirical field of new home-care services, which have emerged 20 years ago, and provided to elderly dependents in Wallonia.
Interdisciplanary
Keywords: economics of the elderly; economics of the handicapped; feminist economics; health; non-labor market discrimination; non-labour market discrimination; personal; professional; and business services; social innovation

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Sociology; Economics
Keywords: criticism of economism; formal economy; general economics

Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
History; Sociology
Keywords: capitalisme; fascisme; marché; socialisme